AB0956 VERTICAL NAIL RIDGING IN PATIENTS WITH FIBROMYALGIA: FREQUENCY, PROPOSED GRADING AND CORRELATION WITH OTHER DISEASE FEATURES. (2nd June 2020) - Moshrif, A.; Abdelkareem, M.; Moneer, M.; Mosallam, A.; Ismail, A.; Elwan, M.; Saad, A.; Abdelaziz, T.
Abstract : Background: The vertical nail ridging (VNR) has long been reported to be related to stressful conditions 1 Objectives: to evaluate the frequency of VNS in FM patients and its relation to other disease parameters depending on a proposed grading. Methods: VNR has been searched for in 212 FM patients (2016 criteria). The number of fingers, the degree of VNR according to this proposed grading (0: no ridging, 1: ridging only detected by a magnifying lens, 2: ridging seen by naked eye and 3: ridging that can be seen and felt) and other FM features according to the new and old ACR criteria have been recorded. 80 subjects of those consulting for knee osteoarthritis have been examined for VNR and those found positive were asked about the FM features and examined for tender points. Patients aged >50 years and those with psoriasis and fungal infections were excluded. Results: the mean age of patients was 32.4±9.9 (73.6% were female). The mean disease duration was 5.8±3.7, while the means of WPI, SSS and tender points were 9.4±2.9, 7.3±1.2 and 14.7±2.3 respectively. VNR was found in 209 patients (98.6%). Of 80 controls, VNR has been found in 61 subjects, of whom FM has been diagnosed in 32 patients (52.4%) by 2016 FM criteria and in 46 (75.4%) by 1990 criteria. The number of fingers with VNR has been found only correlated with the disease duration (r= 0.276, P = 0.000). The severity of VNR was significantly correlating with fatigue (P= 0.002), sleep disturbance (P= 0.001), awaking unrefreshed (P = 0.000), WPI (p = 0.01) and mean tender points (P =0.02). Considering the 2016 criteria as a gold standard, the sensitivity of VNR was 98.37%, the specificity was 9.68% and the diagnostic accuracy was 82.8%. Conclusion: vertical nail ridging is a frequent finding and can be considered helpful for diagnosis of patients with FM. Further studies are needed to validate this sign for diagnosis and follow up of FM patients. References: [1]American Academy of Dermatology. (2007, November 12). Feeling Stressed? How Your Skin, Hair And Nails Can Show It. Science Daily . Retrieved December 30, 2019 from www.sciencedaily.com/releases/2007/11/071109194053.htm Disclosure of Interests: None declared